The Association between Degree of Diabetic Peripheral Neuropathy with Ankle Brachial Index, Toe Brachial Index, and Transcutaneus Partial Oxygen Pressure in Patients with Type 2 Diabetes Mellitus - Asir, Taufik Rizkian; Antono, Dono; Yunir, Em; Shatri, Hamzah (Jurnal Penyakit Dalam Indonesia, 2020)
Introduction. Diabetic peripheral neuropathy (DPN) in the lower extremity caused by complications of diabetes in the microvascular which can damage nerve in the lower extremity. Then, it is necessary to be aware of the process of aterosclerosis elsewhere, both in the macro and microvascular arteries in the lower extremity. This study was conducted to assess the association of the degree of diabetic peripheral neuropathy assessed by Toronto clinical scoring system (TCSS) with the process of atherosclerosis in the blood vessels of the lower extremity, both macrovascular with ankle brachial index (ABI) and toe brachial index (TBI), as well as microvascular with transcutaneus partial oxygen pressure (TcPO2 ) in patients with type 2 diabetes mellitus. Methods. Cross-sectional study was carried out in patients with type 2 DM with DPN with TCSS values> 5 in the Integrated Cardiac Polyclinic, Endocrine and Metabolic Polyclinic, and Internal Medicine Polyclinics at Cipto Mangunkusumo Hospital. Data were obtained from interviews, medical records, as well as ABI, TBI and, TcPO2 examinations. Bivariate analysis of each variable was performed using Spearman test. Results. Total of 36 subjects who met the selection criteria were included in the study, the average age was 62 years (SD 9.2) with 20 (55.6%) of whom were women and the median duration of diabetes was 12 years. Based on bivariate analysis with the Spearman test, there was a statistically significant negative correlation with moderate correlation coefficient between the degree of diabetic peripheral neuropathy assessed by TCSS with ABI (r = -0.475, p = 0.003) and TBI (r = -0.421, p = 0.010). The TcPO2 examination also found a statistically significant negative correlation with moderate correlation coefficient (r = -0.399, p = 0.016). Conclusion. There is a statistically significant negative correlation between the degree of diabetic peripheral neuropaty with ABI, TBI, and TcPO2 examinations.